Deskripsi Keterampilan Kolaborasi Peserta Didik pada Model Pembelajaran Aktif Tipe Quiz Team Kelas VIII SMP Negeri 55 Makassar (Studi pada Materi Pokok Sistem Pernapasan pada Manusia) - Nurul Huda; Sitti Rahma Yunus; Nurhayani H. Muhiddin (Celebes Science Education, 2025)
This study aims to determine "How high is the level of collaboration skills of grade VIII students of SMP Negeri 55 Makassar who are taught using the Quiz Team Type Active Learning Model". This type of research is Pre-Experimental Designs research and One-Group Pretest-Posttest Design research design. The population of this study was grade VIII.1 students at SMP Negeri 55 Makassar. The sample was selected by the Saturated Sampling technique and obtained class VIII.1 17 students as a class given treatment. The research instrument is in the form of a collaboration skills observation sheet consisting of 5 aspects of collaboration skill indicators. The data were analyzed with descriptive statistics. The results of the study concluded: The level of collaboration skills of grade VIII students at SMP Negeri 55 Makassar who were taught using the Active Learning Model Quiz Team Type for the percentage of collaboration skill scores were 42.4% in the first meeting with the sufficient category, 48.2% in the second meeting with the sufficient category and 53.2% in the third meeting with the sufficient category.